"I'm not homosexual or heterosexual, I'm paedosexual": exploring sexual preference for children using interpretive phenomenology. Issue 2 (8th May 2017) - Walton, Jamie S.; Duff, Simon
Abstract : Purpose: There is little research that examines the experiences of individuals who were assessed as having a sexual preference for children. The purpose of this paper is to investigate the lived experience of five incarcerated participants who possessed a sexual preference for either prepubescent or pubescent children and had completed an accredited programme for males convicted of sexual offences in HM Prison Service in England and Wales. Design/methodology/approach: Semi-structured interviews were carried out and the data were analysed using the principles of an interpretative phenomenological approach. Findings: Three recurrent themes were identified. These were: internal battle, I am always going to have these thoughts, and there is no help out there. In particular, these participants perceived that their sexual preference was relatively enduring and would require continuous management. Practical implications: The results have implications for clinical practice and further research. Clinicians may need to think particularly creatively about their therapeutic plans and extend the parameters of desirable treatment goals for clients with sexual preferences for children. Originality/value: To date there are very few studies that have examined the accounts of men with a sexual preference for children regarding their lived experience. Paedophilia constitutes a stable sexual preference, suggesting that convicted perpetrators with such a preference face an inherent problem. Whilst sexual urges may be regulated and arousability reduced, the underlying attraction may remain intact. In response to the lack of research in this area, the aim of this study was to investigate the lived experience of a sexual preference for children.